OPTIMIZATION OF NUSA PENIDA ELECTRICAL SYSTEM: A SIMULATION APPROACH FOR COST AND EMISSION REDUCTION - Vidi Santoso, Mikhael
Nusa Penida is one of Indonesia's outer islands, territorially part of Bali Province. The electrical system in this area is separate from Bali's electrical grid and is supplied by a 20 kV interconnection from a hybrid solar-wind-diesel power station, which connects Nusa Penida, Nusa Lembongan, and Nusa Ceningan islands. The average solar radiation is 5.34 kWh/m²/day with an average wind speed of 4.4 m/s. These conditions can be utilized to develop renewable energy generation in the region. This paper discusses the feasibility of the hybrid power plant established under the natural conditions and the equipment specifications used in the hybrid system in Nusa Penida, taking into account economic factors and the emissions produced. The expected outcome is to determine how the lowest LCOE can be achieved, as well as emission reduction factors, to create the most optimal electrical system structure.